Intersemioosin jäljillä: Sandro Botticellin teokset semiotiikan ja käännöstieteen rajapinnassa - Limnell, Heidi (Suomen kääntäjien ja tulkkien liitto – Finlands översättar- och tolkförbund ry, 2026)
This article approaches the concept of intersemioticity at the intersection of translation studies and semiotics, focusing particularly on Peircean tripartite semiosis. The theme is considered in the context of the Renaissance and the Neoplatonic atmosphere of 15th-century Florence. Three works by Sandro Botticelli — The Birth of Venus, The Story of Nastagio degli Onesti I, and one example from his Dante drawings: Purgatorio XXXII — are examined to illustrate how meanings change and transfer between different sign systems in the intersemiosis when a verbal text is translated into a visual one or when an intersemiotic transfer occurs intervisually. Alongside abductive translation as the primary image analysis method, the analysis employs Peirce's theory of signs and Dinda L. Gorlée’s notion of semiotranslation to examine works of art as active systems of meaning-making processes. The aim is to demonstrate that relationships between works of art constitute dynamic, not merely iconographic nor aesthetic, networks of meaning.